ANALISIS PERBEDAAN PENGARUH INFORMASI LABA DAN RUGI TERHADAP KOEFISIEN RESPON LABA - Titriadi, Brian; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2012)
The aim of this study is measuring the market reaction toward the information contents of earnings and losses. The huge of market reaction can be seen from the amount of earnings responses coefficient that earnings (losses) has. Research carried out by testing the influence of toward PEPS, LEPS, PORD, LORD, POP, LOP, PFIN, LFIN, PEXT, TAX earnings response coefficients (ERC). This study is using earnings-book value capitalization models that devided into three research models and purposive sampling methode for taking sample. Based on the criteria of purposive sampling, data is obtained 300 manufacture companies over a three year period of observation. Then, there are 86 samples that included outlier should be excluded from samples of observation. So, sample which is used for this study is 214 manufacture companies. Analysis technique which is used in this study is multilinier regression of ordinary least square and hypotheses test used partial t test and adjusted R square. Based on analytical results shows that variable PEPS, PORD, POP, and LFIN have significant influence toward earnigs response coefficient (ERC), while variable LEPS, LORD, LOP, PFIN, PEXT and TAX doesn’t have significant influence toward earnings response coefficient (ERC). Explanatory Power of the research models decrease These is shown by adjusted R ² of the models are 0,227 (Model 1), 0.212 (Model 2), 0.111 (Model 3).